Herbivoria por molusco nativo pode reduzir o sucesso de invasão de Hydrilla verticillata. - Oliveira, Marcelo Volta Cortes de (2017)
Biological invasions have received considerable attention in recent decades, for causing many ecological and economic impacts on the invaded ecosystems. The presence of native species has been pointed out as a way to hamper propagation invasive species due to biotic resistance exerted by native species over invasive species. In this study was tested experimentally, the grazing effect of native mollusk Pomacea canaliculata over invasive macrophyte species Hydrilla verticillata and the native one Egeria najas to evaluate the biological interaction as a form of biotic resistance. Both species of macrophytes were offered individually and combined as food resources to the mollusk to evaluate its feeding preference. The macrophytes were evaluate according their calorimetry and malleability (i.e., indicatives of energy availability and palatability, respectively). The results indicate a higher H. verticillata biomass consumption by P. canaliculata when such macrophyte was available both individually and combined with E. najas, suggesting a snail feeding preference for the invasive macrophyte species. In fact, the highest values of calorimetry and malleability were record for H. verticillata, which indicates invasive species presents greater energetic availability and palatability than the native species E. najas. Therefore, aquatic environments where there is the presence of P. canaliculata may characterize habitats with higher biotic resistance to H. verticillata invasions, because both feeding preference and high rates of herbivory showed by this snail on H. verticillata. Native mollusk P. canaliculata can be considered a potential biological controller over invasive macrophyte species. Finally, it is suggested experiments in which both food resource availability and native mollusk densities could be altered in a way to evaluate how the different biological control capacities by the native mollusk act over different invasion scenarios.